Assessment of Drinking Water Quality in Kathmandu, Kirtipur, and Siraha, Nepal - Yadav, Brahamdeo; Maharjan, Jasana; Chaudhary, Sunil; Nath, Deepak; Adhikari, Manoj Kumar; Yadav, Yog Prakash; Yadav, Ramhit; Yadav, Chandradip Kumar; Bhattarai, Ajaya (Tribhuvan University Journal, 2025)
In the present study, the assessment of the water quality of tap water from the spring source, hand pump, and well water from Kirtipur, Siraha, and Kathmandu, respectively, was carried out by determining the physicochemical and microbial characteristics of water samples. Three water samples, one from each source, were collected and analyzed using the standard method of APHA 2017. The different water quality parameters, such as temperature, pH, Electrical Conductivity (EC), Total Hardness (TH), turbidity, iron, ammonia, aluminum, arsenic, and major anions such as Nitrate (NO3-), Chloride (Cl-), Sulphate (SO4 2-), Fluoride (F-) as well as microbial parameter were determined. The physicochemical parameters of the water samples were within the permissible limits of the NDWQS standard. The pH of the studied water samples was slightly basic in nature, ranging from 7.3 to 7.7. In comparison with tap water and hand pump, well water sample from Kathmandu was with high EC, turbidity, TH, Cl-, iron, ammonia, NO3-, SO4 2- and arsenic (As) with value 1167 µs/cm, 1.5 mg/L, 422 mg/L, 135.6 mg/L, 0.11 mg/L, 1.2 mg/L, 17.7 mg/L, 10 mg/L and 0.01 mg/L, respectively. The prevalence of the anions in the water samples was in the order Cl- > NO3- > SO4 2- > F-. The water from the hand pump and well was free from microbial contamination. However, E coli was detected in tap water from Kirtipur, exceeding the NDWQS limit, which indicates the potential risk to public health on direct consumption of water. Regular and strict monitoring of water sources and public awareness on water pollution are highly encouraged.